LANGUAGE POLICIES, REPRESENTATIONS, AND PRACTICES OF STUDENTS IN UFES’ LANGUAGE AND LITERATURE COURSES (PERcursos Linguísticos, 2026)
This text, in light of the literature on Language Policies, has two objectives: (i) to analyze the language policy of the Federal University of Espírito Santo (UFES) and (ii) to investigate the perceptions and practices of students in the Languages and Literature Department (DLL) regarding national and local linguistic diversity, as well as their knowledge of language policies in general and of UFES in particular. The qualitative research involved a literature review, documentary analysis and a public opinion survey. The results show that: (i) among the participants: (a) there is greater interest in English and Spanish, languages present in Basic Education; (b) although many have discussed plurilingualism on the course, few have taken part in specific projects; (c) the majority do not feel prepared to deal with linguistic diversity in teaching and are unaware of Ufes' language policy; (ii) in terms of document analysis: (a) an institutional policy focused on external demands (internationalization) is observed, neglecting local (Ufes and the state) and national linguistic diversity. Although this is a pilot study, we conclude that UFES and the DLL could invest more attention in language policies, promote diversity and request a revision of the institutional policy.
Keywords: Language Policies; Ufes; Languages and Literature Department; Plurilingualism